Elemental and lead isotopic composition of atmospheric particulate measured in the Arctic region (Ny-Ålesund, Svalbard Islands) - Bazzano, Andrea; Ardini, Francisco; Grotti, Marco; Malandrino, Mery; Giacomino, Agnese; Abollino, Ornella; Becagli, Silvia; Traversi, Rita; Udisti, Roberto; CAPPELLETTI, David Michele (Rendiconti Lincei, 2016)
Size-segregated (PM10) aerosol samples have been systematically collected at Ny-Ålesund (Svalbard Islands, Norwegian Arctic) during the spring and summer 2010 and analysed for elemental composition (major and trace elements, rare earth elements) and stable lead isotope ratios (206Pb/207Pb, 208Pb/207Pb). The analysis of the obtained dataset provided valuable information on the sources and long-range transport processes of atmospheric particulate and associated contaminants reaching the Arctic. In particular, a seasonal pattern was evident for Ba, Cd, Mn, Mo, Pb (p value ≤0.05), showing a higher input of elements related to anthropogenic emissions in spring compared to summer. Pb isotope ratios clearly showed that the geographic source of the anthropogenic input is subjected to a seasonal shift with an increased contribution of air masses coming from the north Eurasia during spring, and air masses coming from North America during summer. This finding was further corroborated by back-trajectory analysis. Finally, the analysis of the rare earth elements revealed an uniform pattern, without significant differences between the two seasons.